Policy Implementation of the Formation of the Heirloom-Flag Hoisting Troops (Paskibra) in Manado City - Tampi, Joanna F. A.; Bogar, Wilson; Tumbel, Goinpeace H. (Technium Social Sciences Journal, 2025)
The main purpose of this research is to find out, analyze and describe and discuss the implementation of the policy on the formation of the Heirloom-Flag Hoisting Troops (Paskibraka) in Manado City, especially with regard to recruitment and selection as well as the policy of centralizing education and training. The approach used in this research is descriptive qualitative approach. The data collection techniques used are interviews, observation, documentation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. In this study there are three indicators: (1) Recruitment, (2) Selection, and (3) Education and Training Centering. The results showed that the policy has not been fully implemented in accordance with the mandate of the Regulation of the Pancasila Ideology Development Agency of the Republic of Indonesia Number 3 of 2022 concerning the Presidential Implementation Regulation Number 51 of 2022 concerning the Heirloom-Flag Hoisting Troops Program. The ”Desa Bahagia” System where Paskibraka candidates are housed in 1 (one) location for a minimum of 14 (fourteen) days is not implemented in the education and training center. Several obstacles were found in the lack of Human Resources (HR) in the field that handles program implementation, lack of coordination between sections, and then the limited budget. The local government, in this case the National Unity and Political Agency of Manado City as the implementer of the formation program of the Heirloom-Flag Hoisting Troops (Paskibraka) in Manado City, must further examine: a) Budget planning that supports the Paskibraka formation program; b) Availability of human resources, the number of employees in the field specifically handling the Paskibraka program; c Provision of facilities and infrastructure to support the implementation of policies.